2016
DOI: 10.1063/1.4968832
|View full text |Cite
|
Sign up to set email alerts
|

Doping of SnO2 with H atoms: An alternative way to attain n-type conductivity

Abstract: We propose an explanation for the origin of n-type electrical conductivity in SnO2 based on the results obtained from the DFT+U simulations. Two competitive intrinsic point defects, namely oxygen vacancy and hydrogen impurity, have been considered at different positions within the crystalline lattice in order to find out the equilibrium configurations and to analyze corresponding density of states (DOS) patterns along with the electron localization function (ELF). It has been demonstrated that hydrogen could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Meanwhile, the SH-SnO 2 film showed two-fold higher hydrogen intensity than that of the SO-SnO 2 film due to hydrogen incorporation from H-containing species in H 2 O plasma. Notably, hydrogen impurity concentrations in various oxides influence the crystalline structure and electrical properties, like carrier mobility and concentrations [32][33][34]. For example, Husein et al reported that hydrogen-doped indium oxide films showed decreased electron mobility as the hydrogen content was increased to 5.7% [33].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the SH-SnO 2 film showed two-fold higher hydrogen intensity than that of the SO-SnO 2 film due to hydrogen incorporation from H-containing species in H 2 O plasma. Notably, hydrogen impurity concentrations in various oxides influence the crystalline structure and electrical properties, like carrier mobility and concentrations [32][33][34]. For example, Husein et al reported that hydrogen-doped indium oxide films showed decreased electron mobility as the hydrogen content was increased to 5.7% [33].…”
Section: Resultsmentioning
confidence: 99%
“…Due to better synthetic control than that with fluorine doping, p‐type doping with Group III atoms (In, Ga, and Al) or n‐type doping with Group V atoms (Sb doping), which creates shallow levels, was thoroughly explored in recent years. In addition to increasing conductivity, transition‐metal doping is reported to decrease large volume changes upon lithiation/delithiation .…”
Section: Doped Sno2 Lib Anodesmentioning
confidence: 99%
“…Considering that oxygen vacancies are easily detectable by elemental quantifications, and at the same time, hydrogen itself is an element difficult to characterize, it explains why oxygen vacancies have been attributed to the n-type behavior in some semiconductors. The study by Villamagua et al demonstrated numerically that SnO 2 with hydrogen incorporation, with and without oxygen vacancies, exhibits the same magnitude of the free-carrier density, leading to a conclusion that oxygen vacancies do not contribute to the n-type behavior.…”
Section: Resultsmentioning
confidence: 99%